PERBEDAAN PEMAHAMAN ANGGOTA DEWAN TENTANG ANGGARAN DAN PENGAWASAN ANGGARAN PENDAPATAN BELANJA DAERAH - vegirawati, titin (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2014)
This paper describes the differences in understanding of board members on the budget and monitoring region budget (APBD). Understanding the differences in terms of gender board members, educational level, age, political experience, and training. The research object is a member of the legislature in the municipal area of Palembang. researchers used census data collection methods. The analytical tool used is the one way ANOVA test of difference. The results showed that the differences in the understanding of APBD budgeting and monitoring only in the education and training differences. while gender, age, and political experience did not show differences in the understanding of the APBD budgeting and monitoring.